Optimasi Sampling Bersama Roulette-Wheel Sebagai Improve Metode Sample Random Sampling - riadi marta dinata (Jurnal Komputasi, 2024)
The Sample Random Sampling (SRS) method, which is commonly used in sampling, can improve theaccuracy of the results by carrying out leveling techniques based on probability values. Population data wasobtained from the 2019 Indonesian President & Vice Presidential Election Vote Count Results website forLampung Province. The research began with techniques for determining the number of respondents (voters), toa list of polling places (TPS) in which areas should be occupied by quick-count volunteers. The addition of"Roullet-Whell" computing to SRS (ImproveSRS) produces better accuracy values than regular SRS. Researchalso shows that the deviation value of improveSRS is 1.8% from actual data, which is more effective and efficientcompared to SRS without improvement.